LINKS BETWEEN FINANCIAL STATEMENTS AND MANAGEMENT COMMENTARY - Małgorzata Garstka (Polityki Europejskie, Finanse i Marketing)
The author's aim is to identify the links between two reporting systems: financial and nonfinancial.In this article, the connection between the financial statements and the management report will be shown. The work concerns the management report after the introduction of theobligation of non-financial reporting in the form of additional information in this report, or by means of a separate statement on non-financial information.The objective was achieved by means of literature studies in the field of accounting, as well as the analysis of legal acts, based on which the relations between the two reports should bedetermined. Deductive and inductive reasoning and the method of critical, comparative and descriptive analysis and synthesis were used to formulate conclusions. The existence of linksbetween the management report and the financial statement has been demonstrated. These links may pose a risk of repetition and non-compliance. It is desirable that these links should be madeclear to people responsible for drawing up both reports. Particular attention should be paid to the presentation of this information and steps should be taken in the accounting internal controlprocedures and internal audit, perhaps to confirm that the relevant information has been reconciled and to avoid unnecessary repetition.The results of the research show that there are so many connections, including non-financial information, that it is worthwhile to provide them and their verification as a conscious andorganized activity. This will build the image of the company in the eyes of the report readers.